Systematic Review of Patient and Caregiver Involvement in CKD Research - Talia Gutman; Dale Coghlan; Jonathan C. Craig; Chandana Guha; Allison Jaure; Shilpanjali Jesudason; Adeera Levin; David M. White; Javier Recabarren Silva; Anita van Zwieten; David Tunnicliffe; Andrea K. Viecelli; et al. (Kidney International Reports)
Introduction: Limited consumer involvement in chronic kidney disease (CKD) research may reduce its relevance, impact, and transferability into practice and policy. We aimed to describe the current landscape of consumer (patients with CKD and caregivers) involvement in published CKD research. Methods: Electronic databases were searched to August 2023. Articles describing consumer involvement in CKD research were eligible. All text were imported into NVivo for line-by-line coding using descriptive synthesis of these domains: defining involvement, purpose of involvement, selection, stages of the research, resources, and evaluation. Results: We included 106 articles that involved over 4500 consumers from 15 countries. Eighty-two articles (77%) defined consumer involvement, using 8 different terms. Forty-three articles (41%) addressed reasons for involving consumers in research. Consumers were predominantly identified through clinical or patient networks based on demographic or clinical characteristics. Those involved at higher levels (e.g., coresearcher/patient partner) often had medical or academic training. Consumers were rarely drivers or commissioners of research (n = 6, 6%) and were most likely to be involved as informants (n = 81, 76%) with limited decision-making power. Most articles described consumer involvement in priority setting (n = 48, 45%) and research design (n = 57, 53%) with less evidence of involvement in implementation (n = 28, 26%) and evaluation (n = 24, 22%). Barriers included limited resources (i.e., financial, logistical, or training) and the need for tailored solutions continue to exist. Consumer involvement resulted in increased recruitment and retention, richer data, and more useful outputs for end users. Conclusions: Consumers were mostly involved in discrete activities with limited decision-making power. Increasing financial, logistical, and training resources for consumers may support more meaningful involvement. Ongoing evaluation of processes or impacts of consumer involvement, including consistent reporting, is needed to strengthen evidence and practice in CKD research.